COMPARATIVE ANALYSIS OF CBDC AND TAX LAW ENFORCEMENT IN SELECTED COUNTRIES - Ramadhani, Ressita; Farisy, Zakka; Puteri, Dina Silvia (Bank Indonesia, 2025)
This study explores the prospective Central Bank Digital Currency (CBDC) transactions whilst implementing the Automatic Exchange of Information (AEOI) procedures as part of tax law enforcement in Indonesia. The study seeks to address the challenges and opportunities associated with AEOI within a CBDC framework, considering their potential impact on financial transparency, data privacy, and regulatory compliance. Through normative research, comprehensively reviewing relevant literature and policy analysis, the study identifies best practices from other countries, including ASEAN, East Asia, Oceania, The Bahamas, and Sweden, and it aims to develop recommendations for designing an efficient and secure AEOI framework for CBDC transactions in Indonesia. The findings of this study are derived from lessons learnt from selected countries regarding AEOI practices: Australia, Brunei Darussalam, China, Japan, South Korea, Malaysia, New Zealand, and Singapore. Additionally, Sweden and the Bahamas provide aspirational benchmarks for CBDC implementation while simultaneously implementing AEOI. Recommendations are also generated to improve Indonesia’s CBDC and AEOI implementation progress.